Impact of Lavender on Sleep Quality in Young Individuals - Alforaih, Ruyuf Mohammad; Al-Sowayan, Noorah Saleh (European Journal of Applied Sciences, 2022)
Background: Sleep problems are among the most common problems in adults, affecting physical and psychological health and life quality. Lavender is believed to have a positive effect on sleep. Methods: Data were collected from 20 volunteers in the control group (17 women, 3 men) and 20 volunteers in the intervention group (16 women, 4 men), age: 20 to 35, the intervention was drinking a cup of lavender tea daily before bed for two weeks. Results: Lavender may have a positive effect on the depth of sleep and increased activity upon awakening. Conclusion: when bearing in mind the effects of lavender on the amelioration of sleep quality, recommended to use the herbal remedy as a non-pharmacological treated for the amelioration of the sleep quality.